Peran Digital Marketing sebagai Skills Kewirausahaan di Era Society 5.0 - David Hidayatullah; Fahmi Fathur Rohman; Navyandra Kartika Sari (EXERO : Journal of Research in Business and Economics, 2022)
The background in the preparation of this research is to answer the challenge of how the role of digital marketing as one of the entrepreneurial skills in the era of society 5.0. while the purpose of this study is to find out the role of digital marketing in improving entrepreneurship skills in the era of society 5.0 where the current flow of information technology is growing rapidly. to answer the challenges that occur today in the era of technological globalization so that technology literate entrepreneurship skills are needed to be able to increase sales results. The research method used is descriptive qualitative with data analysis used in this study is qualitative data analysis consisting of three flow of activities that occur simultaneously, namely data reduction, data presentation and conclusion drawing. The subjects in this study were business actors around the POLINES campus. The results showed that increasing entrepreneurship skills through digital marketing skills can increase the sales results of business actors. The implication that can be applied in this research is that the use of improving entrepreneurship skills is not only in the process of producing and selling, but also requires skills/skills in introducing business products so as to increase sales results.